INCREASING INTEREST IN READING IN ESTABLISHING A CRITICAL AND TOLERANT MULTICULTURAL COMMUNITY READING CULTURE - Asep Saepurokhman; Riki Nasrullah; Arip Budiman (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
This study aims to provide a discourse on the importance of increasing reading interest in forming a critical and tolerant multicultural society reading culture. These research studies are literature from various sources that discuss reading interest, reading culture, and its relationship with a multicultural society. The study results that have been carried out show that reading activities can broaden the horizons and horizons of human thinking so that they are not left behind by the rapid development of the times. Everyone must be encouraged to have high interest, activity, and reading habits. Low interest, hobbies, activities, and reading habits can be factors for the decline in the level of progress of a nation. Intolerance, feeling the most correct, the best, and not wanting to respect the opinions, behaviors, and cultures can arise because of low insight, intelligence, and thinking horizons. Therefore, to create a multicultural society that is critical, tolerant, open, and pluralistic, it is necessary to have high reading activities, habits, and culture. This needs to be realized because a high reading tradition can support the acceleration of people's intelligence in responding to various life problems in a nation